The Arabidopsis thaliana Class II Formin FH13 Modulates Pollen Tube Growth - Kollárová, Eva; Baquero Forero, Anežka; Cvrčková, Fatima (Frontiers in Plant Science, 2021)
Formins are a large, evolutionarily conserved family of actin-nucleating proteins with additional roles in regulating microfilament, microtubule and membrane dynamics. Angiosperm formins, expressed in both sporophytic and gametophytic tissues, can be divided into two subfamilies, Class I and Class II, each often exhibiting characteristic domain organization. Gametophytically expressed Class I formins have been documented to mediate plasma membrane-based actin assembly in pollen grains and pollen tubes, contributing to proper pollen germination and pollen tube tip growth, and a rice Class II formin, FH5/RMD, has been proposed to act as a positive regulator of pollen tube growth based on mutant phenotype and overexpression data. Here we report functional characterization of the Arabidopsis thaliana pollen-expressed typical Class II formin FH13 (At5g58160). Consistent with published transcriptome data, live-cell imaging in transgenic plants expressing yellow fluorescent protein-tagged FH13 (FH13-YFP) under the control of the FH13 promoter revealed expression in pollen and pollen tubes with non-homogeneous signal distribution in pollen tube cytoplasm, suggesting that this formin functions in the male gametophyte. Surprisingly, fh13 loss of function mutations do not affect plant fertility but result in stimulation of in vitro pollen tube growth, while FH13-YFP overexpression inhibits pollen tube elongation. Pollen tubes of mutants expressing a fluorescent actin marker exhibited possible minor alterations of actin organization. Our results thus indicate that FH13 controls or limits pollen tube growth, or, more generally, that typical Class II formins should be understood as modulators of pollen tube elongation rather than merely components of the molecular apparatus executing tip growth.